Perspectives of Psychosocial Risk Factors in Cardiovascular Disease - Muhammad Amin Khan, Samia Sarwar, Naeem Amjad, Farrukh Sarrfraz, Qurratulain Mehfooz, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The acknowledgment that psychosocial risk factors contribute to the pathogenesis of cardiovascular malady has driven to the improvement of a new field of behavioral cardiology. The starting driving force for this field was considers performed within the 1980s and 1990s that given epidemiological prove and a pathophysiological premise for a solid connect between a number of psychosocial chance components and cardiovascular illness, counting misery, uneasiness, threatening vibe, work stretch, and destitute social support. In later a long time, extra psychosocial hazard components have been recognized, counting negativity; other shapes of chronic stress, such as childhood abuse and injury, and the mental stretch that will be related with constant medical ailment; need of life reason; and the disorder of “vital exhaustion,” which comprises of a set of three of fatigue, demoralization, and crabbiness. Objective: To determine the Perspectives of Psychosocial Risk factors in Cardiovascular Disease Material and Methods Study design: Quantitative cross sectional Settings: Niazi welfare foundation teaching hospital Sargodha Duration: Three months i.e. 1st January 2022 to 30th March 2022 Data Collection procedure: Cross sectional was conducted on 100 patients. Data was collected by validated questionnaire. The informed consent was taken from all the patients having cardiovascular disease included in the study. Each patient demographic profile was recorded. Psychosocial risk factors included wealth and personal life style stress was calculated. Validated questionnaire was administered to check the stress at home and at work. Data was analyzed by using SPSS version 22. Results: The total number of patients was 110 in which 92 were males and 50 females. According to age 10 patients was in 30-40 age group, 52 was in 41-50, 40 was in 51-60 and 8 was above 60 year of age. The different level of stress as low moderate and high was calculated against Educational, Area and Marital status of patients. Conclusion: Physical and psychosocial chance components at work may act freely to extend dangers or they may too associated to encourage increase the dangers of self-detailed back disorders. There is critical need of developing measuring tool for assessing psychosocial stress level. Keywords: Stress, Psychosocial factor, Behavioral Cardiology, Cardiovascular disease.